Endoscope-assisted versus conventional neck dissection in patients with oral cancer: a systematic review and meta-analysis - Yi-Chan Lee; Li-Jen Hsin; Shih-Wei Yang; Ming-Shao Tsai; Yao-Te Tsai; Che-Fang Ho (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Neck dissection is an integral component of the treatment of head and neck cancers. The present meta-analysis aimed to compare the use of endoscope-assisted neck dissection (END) with conventional neck dissection (CND) in the existing English literature. Methods A search of PubMed (MEDLINE), Embase, and the Cochrane Library for articles reporting the results of the two techniques of neck dissection was completed independently by two individuals. The authors analyzed the data from each study using a random-effects model. Results The pooled analysis demonstrated comparable lymph node yield, intraoperative blood loss, incidence of locoregional recurrence, and incidence of complications between the two groups. A significantly longer operative time but a shorter length of hospital stay was observed in the END group compared with the other group. Conclusions Compared with conventional techniques, END offers similar oncologic outcomes and complication rates; however, it requires a longer operative time. Future studies with long-term follow-up and assessment of patient satisfaction are needed to confirm the clinical use of END. Graphical abstract